2015
DOI: 10.1016/j.ijrobp.2015.07.221
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Prophylactic Cranial Irradiation With Hippocampal Avoidance in Limited Stage Small Cell Lung Cancer

Abstract: The recently reported Chest Radiotherapy Extensive Stage Trial (CREST) showed that administering thoracic radiation therapy (TRT) after a response to first-line chemotherapy improves 2-year overall (OS) and progression-free survival, without an increase in adverse events, in patients with extensive stage small cell lung cancer (ES-SCLC). We evaluated the cost-effectiveness of adding TRT to chemotherapy and prophylactic cranial irradiation (PCI) in ES-SCLC patients. Materials/Methods: Using a partitioned surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The assessed publications received a high-quality score, ranging from 73.1 to 91.7% (see Table 2 ). Four publications could not be assessed in this way as they were abstracts or posters only and therefore could not be scored [ 22 , 26 28 ]. However, due to the paucity of data retrieved from the primary search, these publications were included in the final SLR.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The assessed publications received a high-quality score, ranging from 73.1 to 91.7% (see Table 2 ). Four publications could not be assessed in this way as they were abstracts or posters only and therefore could not be scored [ 22 , 26 28 ]. However, due to the paucity of data retrieved from the primary search, these publications were included in the final SLR.…”
Section: Resultsmentioning
confidence: 99%
“…Several publications reported on direct costs of extensive-stage SCLC specifically [ 12 , 15 19 , 21 , 22 , 25 , 27 ]. Kang et al investigated the costs of SCLC management and found that the median cost of lung cancer in Australia was highest for limited-stage SCLC ($19,046 vs. $12,688 for extensive-stage) [AU$, review of patient records 2005–2008, applying 2005 Australian Medicare Benefits Schedule costings, adjusted to 2016 US$].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations